THE INTERACTIVE RELATIONSHIP BETWEEN COMMITMENT TO UNION AND JOB COMMITMENT: THE NIGERIAN EXPERIENCE (Web of Teachers: Inderscience Research, 2024)
This study investigates the relationship between union commitment and job commitment in the Ni-gerian workplace. The research sample consists of 288 full-time employees, randomly selected from both managerial and non-managerial positions across ten major oil and gas companies lo-cated in the Niger Delta region. Employing a quasi-experimental research design, data were col-lected through a cross-sectional survey that is appropriate for administrative sciences. Data anal-ysis was conducted using Kendall’s Coefficient of Concordance via the Statistical Package for So-cial Sciences (SPSS) version 25. The results indicate a significant negative correlation between union commitment and job commitment within the Nigerian oil and gas sector. This suggests that heightened commitment to labour unions may adversely affect employees' commitment to their jobs. Therefore, employees exhibiting high levels of union commitment in this industry may demonstrate diminished job commitment. Based on this finding, the study concludes that employ-ees’ commitment to unions significantly impedes their job commitment within the Nigerian oil and gas industry, underscoring theoretical and managerial implications.